PENDEKATAN SISTEM DALAM PENANGANAN KESELAMATAN JALAN - Vita Mayastinasari (Journal of Indonesia Road Safety, 2018)
Various traffic safety efforts that aimed to reduce the number of traffic accident victims on road. Traffic safety is a program to reduce the number of accidents either the consequences. Tendency of road accident causes are human factor, therefore is needed a system approach to handle traffic safety that include four aspects, that is 1) Process; 2) Infrastructure; 3) Management; 4) Coordination and integration. Safer road can not be achieved if only just using the strategy, but the capacity of institution is needed by coordination and integration amongst the ministries of the institution. Coordination and integration as a form of synergy among the ministries of the institution to handle the road safety conducted by sharing the role to handle various road safety related areas by using the Information Resources Information System – IRIS. Berbagai upaya keselamatan lalu lintas yang bertujuan menurunkan korban kecelakaan lalu lintas di jalan. Keselamatan lalu lintas merupakan suatu program untuk menurunkan angka kecelakaan beserta seluruh akibatnya. Kecenderungan penyebab kecelakaan lalu lintas adalah faktor manusia, sehingga diperlukan pendekatan sistem dalam penanganan keselamatan jalan yang mencakup empat aspek, yaitu: 1) Proses; 2) Infrastruktur; 3) Manajemen; 4) Koordinasi dan integrasi. Keselamatan jalan tidak dapat terwujud hanya dengan menggunakan strategi, namun dibutuhkan kapasitas kelembagaan melalui koordinasi dan integrasi antar kementerian lembaga. Koordinasi dan integrasi sebagai wujud sinergitas antar kementerian lembaga dalam penanganan keselamatan jalan dilakukan dengan berbagi peran dalam menangani berbagai bidang yang terkait keselamatan jalan dengan menggunakan sistem informasi sumber daya informasi (Information Resources Information System-IRIS).